One‐Step Synthesis of 3, 4‐Disubstituted 2‐Oxazolidinones by Base‐Catalyzed CO2 Fixation and Aza‐Michael Addition. Issue 44 (24th July 2019) - Mannisto, Jere K.; Sahari, Aleksi; Lagerblom, Kalle; Niemi, Teemu; Nieger, Martin; Sztanó, Gábor; Repo, Timo
Abstract: 2‐Oxazolidinones are saturated heterocyclic compounds, which are highly attractive targets in modern drug design. Herein, we describe a new, single‐step approach to 3, 4‐disubstituted 2‐oxazolidinones by aza‐Michael addition using CO2 as a carbonyl source and 1, 1, 3, 3‐tetramethylguanidine (TMG) as a catalyst. The modular reaction, which occurs between a γ‐brominated Michael acceptor, CO2 and an arylamine, aliphatic amine or phenylhydrazine, is performed under mild conditions. The regiospecific reaction displays good yields (av. 75 %) and excellent functional‐group compatibility. In addition, late‐stage functionalization of drug and drug‐like molecules is demonstrated. The experimental results suggest a mechanism consisting of several elementary steps: TMG‐assisted carboxylation of aniline; generation of an O ‐alkyl carbamate; and the final ring‐forming step through an intramolecular aza‐Michael addition. Abstract : Base makes CO2 stick : 1, 1, 3, 3‐Tetramethylguanidine (TMG) catalyzes the one‐step synthesis of 3, 4‐disubstituted 2‐oxazolidinones by an aza‐Michael addition using CO2 as a carbonyl source. The modular reaction occurs between a γ‐brominated Michael acceptor, CO2 and an arylamine, aliphatic amine or phenylhydrazine. The method displays high yields (av. 75 %) and enables late‐stage functionalization of complex drug‐like molecules.